Two Survivor Pathways That Allow Growth in the Absence of Telomerase Are Generated by Distinct Telomere Recombination Events - Chen, Qijun (American Society for Microbiology, 2001)
Yeast cells can survive in the absence of telomerase RNA, TLC1, by recombination-mediated telomere elongation. Two types of survivors, type I and type II, can be distinguished by their characteristic telomere patterns. RAD52 is essential for the generation of both types of survivors. Deletion of both RAD50 and RAD51 produces a phenotype similar to that produced by deletion of RAD52. Here we examined the effects of the RAD50 and the RAD51 epistasis groups as well as the RAD52 homologue, RAD59, on the types of survivors generated in the absence of telomerase. rad59 mutations completely abolished the ability to generate type II survivors, while rad50 mutations decreased the growth viability of type II survivors but did not completely eliminate their appearance. Mutations in RAD51, RAD54, and RAD57 had the converse affect: they eliminated the ability of cells to generate type I survivors in a tlc1 strain. The triple mutant, tlc1 rad51 rad59, was not able to generate survivors. Thus either type I or type II recombination pathways can allow cells to survive in the absence of telomerase; however, elimination of both pathways in a telomerase mutant leads to the inability to elongate telomeres and ultimately cell death.